The effectiveness of computerized clinical guidelines in the process of care: a systematic review - Galasso Rocco; Sicuro Lorella; Almiento Roberta; Colosimo Simona C; Pinnarelli Luigi; Damiani Gianfranco; Sommella Lorenzo; Ricciardi Walter (BMC, 2010)
Abstract Background Clinical practice guidelines have been developed aiming to improve the quality of care. The implementation of the computerized clinical guidelines (CCG) has been supported by the development of computerized clinical decision support systems. This systematic review assesses the impact of CCG on the process of care compared with non-computerized clinical guidelines. Methods Specific features of CCG were studied through an extensive search of scientific literature, querying electronic databases: Pubmed/Medline, Embase and Cochrane Controlled Trials Register. A multivariable logistic regression was carried out to evaluate the association of CCG's features with positive effect on the process of care. Results Forty-five articles were selected. The logistic model showed that Automatic provision of recommendation in electronic version as part of clinician workflow (Odds Ratio [OR]= 17.5; 95% confidence interval [CI]: 1.6-193.7) and Publication Year (OR = 6.7; 95%CI: 1.3-34.3) were statistically significant predictors. Conclusions From the research that has been carried out, we can conclude that after implementation of CCG significant improvements in process of care are shown. Our findings also suggest clinicians, managers and other health care decision makers which features of CCG might improve the structure of computerized system.